2021
DOI: 10.3390/ijgi10100711
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Retrieval Using Polarimetric SAR Data and Experimental Observations in an Arid Environment

Abstract: Soil moisture is a critical component for Earth science studies, and Synthetic Aperture Radar (SAR) data have high potential for retrieving soil moisture using backscattering models. In this study, polarimetric SAR (PALSAR: Phased Array type L-band Synthetic Aperture Radar) data and polarimetric decompositions including span, entropy/H/alpha, and anisotropy, in combination with surface properties resulting from field and laboratory measurements, are used to categorize the natural surface condition and discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The Dubois model is a semi-empirical model used to retrieve surface soil moisture with vegetation cover [10], and Dave et al [11] modified the Dubois model to estimate soil moisture for a winter wheat crop, finding a better estimation in the early and mature stages of crop growth. Gharechelou et al [12] compared the Dubois model and Oh model with observational soil moisture data and found that the Oh model showed more accurate results in a dry environment, which is more suitable for a wider range of surface roughness and shorter wavelengths, while the Dubois model overestimated the values. However, these models were traditionally applied in remote sensing applications for soil moisture retrieval, lacking observational data analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The Dubois model is a semi-empirical model used to retrieve surface soil moisture with vegetation cover [10], and Dave et al [11] modified the Dubois model to estimate soil moisture for a winter wheat crop, finding a better estimation in the early and mature stages of crop growth. Gharechelou et al [12] compared the Dubois model and Oh model with observational soil moisture data and found that the Oh model showed more accurate results in a dry environment, which is more suitable for a wider range of surface roughness and shorter wavelengths, while the Dubois model overestimated the values. However, these models were traditionally applied in remote sensing applications for soil moisture retrieval, lacking observational data analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Soil moisture influences meteorological and climatic processes, although surface soil moisture only constitutes 0.0012% of all water available on the earth [5]. Soil moisture is important in modeling the ecosystem dynamics and the biogeochemical cycles but it has not had widespread application in modeling these processes because it is a variable that is very difficult to measure a spatially comprehensive basis [6]. The soil moisture gives also important information for agriculture irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of radar data to retrieve soil moisture is of considerable importance in many domains, including agriculture, hydrology, and meteorology [6]. Despite many advantages that can be derived from the knowledge of soil moisture distribution, the measurement of soil moisture has a few limitations.…”
Section: Introductionmentioning
confidence: 99%